A PRAGMATIC ANALYSIS OF COMPLIMENT UTTERANCES ON LEGALLY BLONDE MOVIE AND ITS TRANSLATION - VRIANDICA, ADHIVA SETYO (2011)
This research is aimed at describing the variations of the language forms, describing the different expression between male and female, and describing the equivalence of the implicature pattern of compliment utterances on Legally Blonde movie and its translation. In collecting the data, the writer uses documentation method. In analyzing the compliment utterances and its translation, the steps are: finding the variation of forms of utterances by applying language form theory, finding the differences in the way male and female expressing the compliment utterances by applying four types politeness strategy of Brown and Levinson, and describing the equivalences of the implicature by applying Grice theory. Having analyzed the data, the writer finds that the forms of compliment utterances and its translation are word is translated into word; noun phrase is translated into word; noun phrase is translated into noun phrase; noun phrase is translated into declarative sentence; simple declarative sentence is translated into word; simple declarative sentence is translated into adjective phrase; simple declarative sentence is translated into simple declarative sentence; negative declarative sentence is translated into negative declarative sentence; compound sentence us translated into compound sentence; compound sentence is translated into simple declarative sentence; interrogative sentence is translated into interrogative sentence; negative interrogative sentence is translated into declarative sentence; negative interrogative sentence is translated into negative interrogative sentence; and exclamatory sentence is translated into adjective phrase. In the case of politeness strategies the writer finds equivalence in bald on record, positive politeness, negative politeness, and off record; and the non equivalence case the writer finds in negative politeness is translated into positive politeness. In the case of implicature the writer finds the equivalence in source language and target language are conventional implicature is translated into conventional implicature; conventional implicature is translated into conversational implicature; and conversational implicature is translated into conversational implicature.